Geoethics and its impact in Peru - Villacorta Chambi, Sandra Paula (2018)
Geoethics is based on community relation with geoscientist (Amiry & Bohle, 2017). Nevertheless, there are many cases, such as Africa where communities do not concern about geoscience activities because they got not involved before the projects started, a similar situation happened was found in Peru with mining activities. At the beginning of 2014, the Peruvian Section of IAPG (IAPG-Peru) started to share the principles of the IAPG (Peppoloni & Di Capua, 2012). IAPG provides knowledge for ethical work around Geoscience, for their development and successful application (Di Capua et al., 2016). In this sense, IAPG-Peru has gained a great rating with an arduous work of its committee with the support of IAPG and national entities as the Peruvian Geological Society and the Peruvian Geological Survey. During summer 2017, in Peru occurred extreme meteorological events with negative effects on Peruvian society. According to the damage assessment report of the Peruvian Civil Defence Institute, in Lima, these events produced 1,758 collapsed homes, 916 uninhabitable and 10,250 affected in 2017. Nevertheless, after the disaster, many people continue building without appropriate technical support. To avoid this situation, IAPG Peru professionals bring an Open Letter with an exhortation to adopt a series of actions to face extreme meteorological events in order to reduce geo-risks. In this calling, it is mentioned the needing to take up effective initiatives to promote a professional and scientific discussion about land planning in Peru, encouraging they must take actions taking into account the geological and climatic conditions from the country. On the other hand, mining activities in Peru hold geoethics problems, which are highlighted with development of metallic mining in Peru. In the past, tailing dams from mine activity in some cases, tailings have been washed by the Peruvian fluvial system such as Rimac River located in the central part of Peru and a main water resources of the Peruvian capital. Even some communities were affected by contamination (eg. Oroya city). This article shows an overview of attempts to spread Geoethics to Peruvian community and the outline in dilemma relating to geological risk management, mining activity and environmental contamination with some difficulties because of restrictive conceiving in a country with the fastest growing economy.